THE INFLUENCE OF REGISTRATION SERVICE QUALITY AND TRUST ON OUTPATIENT SATISFACTION UNDER BPJS HEALTH INSURANCE GUARANTEE AT HERMINA PALEMBANG HOSPITAL - Elvi Indahwati; Marlina Widiyanti; Muchsin Saggaff Shihab; Aslamia Rosa (Jurnal Ekonomi, 2023)
This research aims to determine the influence of registration service quality and trust on outpatient satisfaction under BPJS Health Insurance guarantee at Hermina Palembang Hospital. The population of this study consisted of outpatient BPJS Health Insurance patients at Hermina Palembang Hospital during the period of 2022-2023, totaling 102,360 respondents. The sample for this study is 123 respondents who are outpatient BPJS Health Insurance patients at Hermina Palembang Hospital during the period of 2022-2023, selected using purposive sampling technique. The results of multiple linear regression analysis show that registration service quality and trust have a positive and significant influence on patient satisfaction. In terms of service quality, the management of Hermina Palembang Hospital is expected to evaluate the factors causing frequent congestion in the outpatient registration process under BPJS Health Insurance. Regarding trust, it is recommended to evaluate the service providers in order to improve the quality of service delivery. The addition of information staff is perceived as necessary to provide assistance to patients in need.